2018
DOI: 10.1016/j.bbadis.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid regulates the autophagy of vascular smooth muscle cells in diabetes by elevating hydrogen sulfide level

Abstract: Dysfunctional vascular smooth muscle (VSM) plays a vital role in the process of atherosclerosis in patients with type 2 diabetes mellitus (T2DM). Alpha-lipoic acid (ALA) can prevent the altered VSM induced by diabetes. However, the precise mechanism underlying the beneficial effect of ALA is not well understood. This study aimed to determine whether ALA ameliorates VSM function by elevating hydrogen sulfide (HS) level in diabetes and whether this effect is associated with regulation of autophagy of VSM cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Recent studies have shown that autophagy induction inhibits both the endothelial dysfunction (Fetterman, et al, 2016;Y. Xie, et al, 2011) in endothelial cells from diabetic patients and phenotypic switching of VSMCs in diabetic vascular lesions (An, Li, Wei, Li, & Xu, 2018;Qiu, et al, 2018). These studies demonstrate a protective role of autophagy in diabetic vascular disorders.…”
Section: Autophagy In Diabetic Medial Calcificationmentioning
confidence: 82%
“…Recent studies have shown that autophagy induction inhibits both the endothelial dysfunction (Fetterman, et al, 2016;Y. Xie, et al, 2011) in endothelial cells from diabetic patients and phenotypic switching of VSMCs in diabetic vascular lesions (An, Li, Wei, Li, & Xu, 2018;Qiu, et al, 2018). These studies demonstrate a protective role of autophagy in diabetic vascular disorders.…”
Section: Autophagy In Diabetic Medial Calcificationmentioning
confidence: 82%
“…Such increment in autophagy expression is in harmony with Hernandez-Gea et al 9 who indicated that activation of HSCs triggers autophagy through providing the required energy resources for their activation, thus leading to the progression of liver fibrogenesis. Furthermore, we showed that the administration of ALA for 8 weeks counteracted this observed upregulated LC3-II expressed levels, which is in coherence with other studies that documented the blockade of autophagy in various cells after treatment with ALA. 21,42,43 Our data postulate that ALA modulates the progression of hepatic fibrosis via a possible correlation between autophagy suppression and inactivation of HSCs. Conversely, other studies showed that autophagic flux was enhanced during attenuation of hepatic fibrosis 44,45 through induction of HSC senescence.…”
Section: Discussionmentioning
confidence: 61%
“… Action Mechanisms Cells/Models H 2 S gas/donor application (concentration) Refs. Promoting mitophagy Activation of Parkin recruited by PINK1 and then ubiquitination of Mfn2 RAECs NaHS (100 μM) [71] Inhibiting mitophagy Phosphorylation of Akt and dephosphorylation of FoxO3a MAECs NaHS (30 μM) [72] Inhibiting autophagy Dephosphorylation of AMPK and phosphorylation of mTOR VSMCs isolated from rat thoracic aorta NaHS (100 μM) [73] Inhibiting autophagy Dephosphorylation of AMPK and activation of Nrf2 RAECs/db/db mice NaHS (100 μM) [74] …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies showed that both supplementation of H 2 S and the overexpression of its synthetases mitigated mitophagy [72] . H 2 S inhibited adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway, which is closely associated with autophagy [73] . On the other hand, the ratio of microtubule-associated protein 1A/1B-light chain 3 (LC3)-II to LC3-I is commonly used as an indicator of autophagy.…”
Section: Physiological Regulation Of Blood Vessels By H 2 mentioning
confidence: 99%